Origin of ultramafic-mafic bodies on the Isles of Lewis and Harris (Scotland, UK): Constraints on the Archean-Paleoproterozoic evolution of the Lewisian Gneiss Complex, North Atlantic Craton - Guice, George L.; Miocevich, Sophie R.; Hughes, Hannah S.R.; McDonald, Iain; Goodenough, Kathryn M.; Ackerson, Michael R.; MacDonald, John M.; Faithfull, John W. (Precambrian Research, 2022)
The Lewisian Gneiss Complex (LGC) is a tonalite-trondhjemite-granodiorite (TTG)-dominated fragment of the North Atlantic Craton (NAC) in northwest Scotland. End-member models describe the LGC as representing either a continuous piece of Archean crust or up to 12 geologically distinct Archean terranes, with interpretations sitting on a spectrum between these end-members. There is particular uncertainty over the correlations between the Archean–Paleoproterozoic magmatic and metamorphic events recorded by mainland part of the LGC and the part exposed on the Outer Hebridean islands of Lewis and Harris. In this paper, we present the results of field mapping, petrography, and major, trace and platinum-group element (PGE) bulk-rock geochemistry for four ultramafic–mafic bodies in Lewis and Harris, namely: Maaruig, Loch Mhorsgail, Coltraiseal Mor and Beinn a’ Chuailean. We consider the effects of metamorphism and element mobility, their petrogenesis, and potential correlations with ultramafic–mafic rocks elsewhere in the LGC. Our data indicate that the studied ultramafic–mafic rocks can be subdivided into two petrologically distinct groups. Metaperidotites and metapyroxenites from Maaruig and Loch Mhorsgail are interpreted as Archean (>2.8 Ga) cumulates distinct from anything currently identified in the mainland LGC, with this interpretation based on distinctive modal layering, a discordance with surrounding TTG gneiss, fractionated PGE patterns ([Pd/Ir]N = 1.3–6.6) and negative HFSE anomalies ([Nb/La]N = 0.2–0.8). Metagabbronorites from Coltraiseal Mor and Beinn a’ Chuailean, which also exhibit negative high field strength-element (HFSE) anomalies ([Nb/La]N = 0.2–0.7) and show mildly fractionated ([Pd/Ir]N = 1.2–2.8) PGE patterns, most likely represent deformed Paleoproterozoic dykes. These occurrences could be correlatives of a suite of ca. 2.4 Ga mafic dykes exposed throughout the mainland LGC (the Scourie Dykes), with the Outer Hebridean occurrences having experienced more intense Paleoproterozoic (Laxfordian) ...